Pengaruh pemberian pakan fermentasi ampas kelapa dan bekatul padi menggunakan Rhiodiotorula taiwanensis UNJCC Y-171 terhadap pertumbuhan larva Black Soldier Fly (BSF) dan komposisi proksimatnya. - Sari, Yunita; Rini Fahmi, Melta; Sukmawati, Dalia (Buitenzorg: Journal of Tropical Science, 2025)
Black soldier fly (BSF) larvae, or maggots, are a promising alternative protein-rich feed for aquaculture. This study aims to evaluate the effect of fermented feed made from coconut pulp and rice bran using the yeast Rhodotorula taiwanensis UNJCC Y-171 on maggot growth and proximate composition. The study was conducted from June to August 2024 at the Universitas Negeri Jakarta and the Ornamental Fish Aquaculture Research Center. The treatments included a control group (K) and fermentation using yeast at 30% (A) and 40% (B) concentrations. Measurements were taken on days 10, 13, 16, and 19. The results showed that fermented feed significantly increased maggot wet weight and body length, particularly in treatment B. On day 16, the wet weight of maggots in treatment B reached 182.00±45.14 g, higher than the control (77,00±52.03 g). The body length of maggots in treatment B was also greater (1.59±0.12 cm) than in the control (1.19±0.09 cm). Proximate analysis indicated that maggots in treatment B had a higher fat content (15.57%) compared to the control (12.11%), while crude fiber content was lower (1.27% compared to 1.63%), indicating improved feed efficiency. Although the protein content in treatment B (12.29%) was slightly lower than in the control (13.27%), fermentation with R. taiwanensis UNJCC Y-171 enhanced nutrient bioavailability. This study confirms that feed fermentation with R. taiwanensis UNJCC Y-171 at a 40% concentration optimally improves both maggot growth and nutritional quality. Therefore, this method has the potential to serve as a more cost-effective alternative feed for aquaculture. Keywords: Rhodotorula taiwanensis, feed fermentation, maggot, proximate analysis, feed efficiency